Case report: Back pseudocyst of unknown origin - Moussally, Moustafa (Int J Surg Case Rep, 2020)
INTRODUCTION: Soft tissue masses are fairly encountered clinical entities. Among the rare forms of soft tissues masses are non-pancreatic pseudocysts which are defined as encapsulated fluid collections not lined by epithelium. We are presenting a rare case of a pseudocyst of the back located within the paravertebral muscles at a tertiary care center. CASE DESCRIPTION: Patient presented with a progressively enlarging painless back mass. CT scan was done which showed a 10 × 10 cm cystic lesion along the paravertebral muscles of the back. Surgical excision of the mass was performed revealing an irregularly shaped multilocular cyst. Final pathology showed the lesion to be a pseudocyst. DISCUSSION: Pseudocysts can arise in a variety of locations such as omentum, adrenal glands, spleen or lungs. The etiology of these pseudocysts is highly variable and can be related to trauma, inflammation, or surgery. The diagnosis of these entities requires proper imaging and histopathologic examination. CONCLUSION: Pseudocysts arise due to a myriad of conditions and their diagnosis remains a challenge. Our case comprises the first reported case of idiopathic pseudocyst of the back. Although rare, pseudocysts should be considered in the differential of unexplained masses.